Kajian Ekonomi Tentang Kemiskinan Di Perdesaan Propinsi Sumatera Barat - Syamsul Amar (Economic Journal of Emerging Markets, 2009)
This research is aimed to study problem of poverty in rural areas of West Sumatera. Operationally, this study has four objectives: (1) to analyze factors determining poverty, such as: land tenure, technology, education, health, access into institutional economies, and alternative profession; (2) to seek the relative poverty as indicated by land tenure distribution and income distribution; (3) to analyze discrepancies in land tenure distribution and income distribution between households clasified poor and not poor; and (4) to analyze discrepancies in income distribution between households with alternative professions and those without alternative professions; One of five hypotheses in this research turn out to be empirically unsupported; The difference between land tenure distribution among households classified not poor is insignificant. This may be due to the fact that this research is carried out in villages whose conditions are quite similar so that land tenure distribution between both categories of households does not vary.